Pengaruh Lama Penyimpanan dan Invigorasi Terhadap Viabilitas dan Vigor Benih Padi Lokal Bangka Aksesi Mayang - Kartika, .; Sari, DK (JURNAL ENVIAGRO, 2015)
In Indonesia, rice is the staple food of most homes in urban and rural areas. Management of post-harvest activity has an important role on the rice seed quality at the storage period. One of the solutions to overcome seed deterioration is to perform invigoration. It can be conducted in some methods; those are osmoconditioning, hydration-dehydration, and matrioconditioning. The purpose of this study is to determine the effects and interaction of storage duration and invigoration toward seed viability and vigor of Bangka local rice accession Mayang. This study was conducted in the Laboratory of Agrotechnology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung form November 2012 to January 2014. Completely Randomized Design Factorial (CADF) was used as design of experiment of this study. The first factor is the storage duration (L) that consist of 3 treatment levels those are L7 = storage duration (7 months), L8 = storage duration (8 months) and L9 = storage duration (9 months), while the second factor is the invigoration treatment which consist of 4 treatment levels, those are K = controls, P = osmoconditioning using PEG 8000, H = hydration-dehydration and A = husk. The results showed that treatment of storage duration and invigoration statistically significant to the seed viability and vigor of Bangka local rice accession Mayang. However, there was no interaction between storage duration and invigoration. The best result was storage duration of 7 months for seed viability and vigor, while hydration-dehydration method was the best result on invigoration treatment.Â